An update on the bridging factors connecting autophagy and Nrf2 antioxidant pathway - Ning, Baike; Hang, Shuqi; Zhang, Wenhe; Mao, Caiwen; Li, Dan (Frontiers in Cell and Developmental Biology, 2023)
Macroautophagy/autophagy is a lysosome-dependent catabolic pathway for degradation of intracellular proteins and organelles. Autophagy dysfunction is related to many diseases including lysosomal storage diseases, cancer, neurodegenerative diseases, cardiomyopathy, and chronic metabolic diseases, in which increased reactive oxygen species (ROS) levels are also observed. ROS can randomly oxidize proteins, lipids and DNA, causing oxidative stress and damage. Cells have developed various antioxidant pathways to reduce excessive ROS and maintain redox homeostasis.Treatment targeting only one aspect of diseases with autophagy dysfunction and oxidative stress shows very limited effects. Herein, identifying the bridging factors that can regulate both autophagy and antioxidant pathways is beneficial for dual-target therapies. This review intends to provide insights into the current identified bridging factors that connecting autophagy and antioxidant pathways, as well as their tight interconnection with each other. These factors could be potential dual-purpose targets for diseases implicated with both autophagy dysfunction and oxidative stress.